Two-linker MOFs-based glass fiber paper monolithic adsorbent for atmospheric water harvesting in arid climates. (1st November 2022) - Luo, Fan; Liao, Tingting; Liang, Xianghui; Chen, Weicheng; Wang, Shuangfeng; Gao, Xuenong; Zhang, Zhengguo; Fang, Yutang
Abstract: With the increasing demand for freshwater resources, the sustainable and effective utilization of atmospheric water has become a critical issue. Herein, an efficient and stable monolithic water-adsorbent is designed via functionalizing glass fiber paper loaded with two-linker metal-organic frameworks (CGF-mixed-MOFs(Al)). Firstly, a chitosan (CTS) polyelectrolyte layer is constructed on glass fiber paper to improve the MOFs loading capacity (306.71%) through electrostatic interaction and hydrophilic interaction. Subsequently, a series of two-linker metal-organic frameworks (mixed-MOFs(Al)) composed of MIL-160(Al) and Al-fumarate are tailor-made on CGF surface through a situ synthesis self-assembly technology. The resultant mixed-MOFs(Al) monolith exhibits better water harvesting ability and faster adsorption kinetics at low humidity owing to possessing more active adsorption sites. Different from CGF-MIL-160(Al) and CGF-Al-fumarate, the water sorption of CGF-mixed-MOFs(Al)5  at 30% RH, 25% RH and 20% RH reaches 0.37 g/g, 0.31 g/g and 0.25 g/g, respectively. The lab-scale atmospheric water harvesting device based on CGF-mixed-MOFs(Al)5 confirms the feasibility of this work-tailored product as a potential water sorbent in low-humidity environments. The cyclability results (50 times) indicate that CGF-mixed-MOFs(Al)5 maintains good water capture performance, integrity (no MOFs leakage) and crystallinity, which guarantees its working reliability and sustainable benefits. Therefore, our customized water adsorption system provides a simple, long-effective, economical and advanced strategy to capture more fresh water from atmosphere in arid climates. Graphical abstract: Image 1 Highlights: The construction of chitosan layer on glass fiber paper promotes high MOFs loading. Two-linker MOFs involving MIL-160(Al) and Al-fumarate is in-stiu synthesized. The water adsorption properties of two-linker MOFs can be adjusted by changing the ratio of organic ligands. The monolithic adsorbent shows high water-harvesting capacity even at low humidity.